Exploring Corporate Stakeholders' Perspectives on Building Capacity for Employee Engagement in Workplace Wellness Initiatives. (April 2022) - Keller, Abiola O; Berman, Rebecca; Scotty, Barb; Pinto, Daniel
Engaging employees with chronic conditions as partners in designing, implementing, and evaluating workplace wellness activities is a promising approach for optimizing the impact of workplace health promotion programs. Yet, there is a need for information on how employees are engaged in this process. We conducted a process evaluation of activities of the Patient-Centered Outcomes Research for Employees (PCORE) project formed around building capacity for employee engagement in wellness initiatives. Individual interviews were conducted with the 11 project stakeholders to explore perspectives of the project's participatory process and activities. Thematic categories emerging in the analysis were (1) Commitment and support, (2) Understanding purpose and roles, (3) Role of employees in wellness programming, and (4) Communication during meetings. This process evaluation provides insights from a model of stakeholder engagement in the corporate setting. Creating an environment that supports meaningfully engaging employees as partners in co-creating workplace wellness initiatives requires effectively addressing the unique aspects of the U.S. corporate culture such as the emphasis on productivity and the prevalent traditional top-down organizational structures.